TiO2 Nanotube Arrays Synthesis, Properties, and Applications - Grimes, Craig A.; Mor, Gopal K. (Springer US : Imprint: Springer, 2009)
TiO2 Nanotube Arrays: Synthesis, Properties, and Applications is the first book to provide an overview of this rapidly growing field. Vertically oriented, highly ordered TiO2 nanotube arrays are unique and easily fabricated materials with an architecture that demonstrates remarkable charge transfer as well as photocatalytic properties. This volume includes an introduction to TiO2 nanotube arrays, as well as a description of the material properties and distillation of the current research. Applications considered include gas sensing, heterojunction solar cells, water photoelectrolysis, photocatalytic CO2 reduction, as well as several biomedical applications. Written by leading researchers in the field, TiO2 Nanotube Arrays: Synthesis, Properties, and Applications is a valuable reference for chemists, materials scientists and engineers involved with renewable energy sources, biomedical engineering, and catalysis, to cite but a few examples. .